Who Owns the Wealth in Tax Havens? Macroevidence and Implications for Global Inequality - Anette Alstadsæter; Niels Johannesen; Gabriel Zucman (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2017)
Drawing on newly published macroeconomic statistics, this paper estimates the amount of household wealth owned by each country in offshore tax havens. The equivalent of 10% of world GDP is held in tax havens globally, but this average masks a great deal of heterogeneity - from a few percent of GDP in Scandinavia, to about 15% in Continental Europe, and 60% in Gulf countries and some Latin American economies. We use these estimates to construct revised series of top wealth shares in ten countries, which account for close to half of world GDP. Because offshore wealth is very concentrated at the top, accounting for it increases the top 0.01% wealth share substantially in Europe, even in countries that do not use tax havens extensively. It has considerable effects in Russia, where the vast majority of wealth at the top is held offshore. These results highlight the importance of looking beyond tax and survey data to study wealth accumulation among the very rich in a globalized world.
Keywords: H26; H87; E21; 330; inequality; wealth; tax evasion; tax havens